Pengaruh Kompetensi Sumber Daya Manusia, Partisipasi Masyarakat dan Proteksi Awig-Awig Terhadap Kencenderungan Terjadinya Kebangkrutan Pada Lembaga Perkreditan Desa (Studi Pada LPD di Kabupaten Buleleng-Bali) - Putu Indah Paramita; I Putu Julianto (Universitas Pendidikan Ganesha, 2021)
As an institution that was formed by traditional villages in Bali, apart from having a business function, the Lembaga Perkreditan Desa (LPD) also had a social function in advancing the economy of the traditional village and all its krama. Disparate of the other financial institutions, apart from using formal organizational rules, LPD also used kinship rules both in decision making and in making the LPD regulations (awig-awig). This study aimed to examine the effect of human resource competence, community participation and the protection of awig-awig to the tendency of bankruptcy at village credit institutions. This research used quantitative methods with the number of samples used were 63 LPD in Buleleng Regency with 189 respondents. The data analysis used Statistical Package for Social Sciences (SPSS) 24.0 by using multiple linear regression test. The results show that human resource competence, community participation and awig-awig protection have a negative effect on the tendency of bankruptcy at LPD.